Molekulare Mechanismen der Membranfusion : Studien mit Liposomen - Arnold, Klaus (Akademie, 1994)
Fusions of membranes occur during key processes in cellular biology. This text describes the biophysical mechanisms of these processes.
Sitzungsberichte der Sächsischen Akademie der Wissenschaften zu Leipzig ; Mathematisch-naturwissenschaftliche Klasse Bd. 124, Hft. 2
Keywords: fúze membrán; histologie; liposomy; Membrane Fusion; cytologie, klinická cytologie; Liposomes